PENGARUH ENVIRONMENTAL KNOWLEDGE, ENVIRONMENTAL CONCERN DAN GREEN BRAND IMAGE TERHADAP GREEN PURCHASE INTENTION DENGAN PERCEIVED PRODUCT PRICE AND QUALITY SEBAGAI MODERATING VARIABLE - Anis Qomariyah; Bulan Prabawani (Jurnal Ilmu Administrasi Bisnis, 2019)
In recent years, public awareness and concern of green products has begun to increase. People are starting to pay attention to the ingredients in all the products they use. This condition triggers companies to create beauty products that are environmentally friendly and safe to use. This study aims to determine and explain the effect of environmental knowledge, environmental concern, green brand image on green purchase intention with perceived product price & quality as a moderating variable. The type of this research is explanatory research with a quantitative approach. The sample used was 100 visitors of The Face Shop Mall Ciputra Semarang. The sampling technique used was purposive sampling and accidental sampling. Data collection methods used were physical questionnaire and online questionnaire. Data processing using SmartPLS 3.2.8. The results of this study indicate that green brand image and the perceived product price & quality significantly influence the green purchase intention. While environmental knowledge and environmental concern do not significantly influence green purchase intention. The moderation type of perceived product price & quality on environmental knowledge is quasi moderator. Whereas the moderating type of variable perceived product price & quality towards environmental concern variables and green brand image is antecendents.